“EdTech Integration Framework in Schools”: Systematic Review of the Literature - Sosa-Díaz, María José; Sierra-Daza, María Caridad; Arriazu-Muñoz, Rubén; Llamas-Salguero, Fátima; Durán-Rodríguez, Noelia (Frontiers in Education, 2022)
The process of integration of Information and Communication Technologies (ICT) in the Educational System is a dynamic process influenced by multiple interdependent factors. The most relevant studies published to date have highlighted the following as systemic levels of ICT integration: teachers, schools and educational policy. The general objective of this work is to carry out a Systematic Literature Review (SLR) on the strategic planning of technology in primary and secondary schools from 2010 to 2021. This study is supported by a qualitative methodology based on a SLR, guided by the PRISMA protocol. For this purpose, a keyword-based document search was carried out in three databases: Eric, Scopus and WOS. For the collection of information, the criteria applied for the inclusion of papers was by date (last twelve years) and type of document (journal articles). A total of 6,187 scientific journal articles were initially included in the CADIMA platform, where finally, after screening, 42 articles were selected that met the established criteria: studies with teachers and students in the educational stages of Primary and Secondary Education, excluding Higher Education. Empirical studies with quantitative and/or qualitative methods are also included, discarding theoretical studies. Research on digital technologies from a general perspective is also considered relevant, excluding studies on specific technologies. This SLR concludes by providing an explanatory theoretical model, defining the integration of ICT in educational centres as a complex, systemic and ecological process, where legislative and organisational structures, such as leadership, strategic planning and collaboration among professionals, are essential elements. Therefore, the incorporation of technology in the classroom requires a redefinition of the organisational culture of schools.